How Different Geographical Areas React to Covid19 Shock : Regional Resilience and Structural Transformation - Siti Maftukhah; Retno Widodo Dwi Pramono (The Journal of Indonesia Sustainable Development Planning, 2022)
In the last 10 years, Covid19 has emerged as an important recent shock that has had an effect on the globaleconomy. Regional resilience may have an effect on how different regions are affected. This study intends tolook at how regional resilience is affected by structural change both before and after Covid19. We identify twodifferent situations (prior to and during the Covid19 shock) that affect whether structural reform increasesregional resilience. The findings show that Covid19 has a number of negative effects on regional resilience.Additionally, raising a sector's productivity has a significant positive effect on resilience under typical conditions(prior to Covid19). A sector's increased productivity and contemporaneous workforce transfer to other sectorswith higher productivity during the COVID19 shock, however, have a significant beneficial effect on regionalresilience. Therefore, when the circumstance is stable, productivity becomes more crucial. However, amid ashock, the industry and its employees' flexibility and agility are more crucial.